Penerapan model pembelajaran kooperatif tipe teams games tournament untuk meningkatkan kemampuan koneksi matematis siswa kelas I: Penelitian Tindakan Kelas pada Pembelajaran Matematika di Kelas I SDN 6 Nagrikaler - Yulianti, Yena; Putri, Hafiziani Eka; Nuraeni, Fitri (IKIP Siliwangi, 2024)
This research was motivated by the low mathematical connection ability of the first-grade students’ at SDN 6 Nagrikaler. Cooperative learning model Teams Games Tournament type is one model that can be applied to improve students’ mathematical connection abilities through games, tournaments, and group collaboration. This study aims to determine the initial conditions of students’ mathematical connection abilities, teacher and student activities during learning, and to determine the increase in students’ mathematical connection abilities after applying cooperative learning model Teams Games Tournament type. This research is Classroom Action Research (PTK) using the Kemmis and Taggart designs for 2 cycles, which contain aspects of planning, action, observation, and reflection. The research subjects consisted of 29 students. The research instruments used were observation sheets and tests. The results showed an increase in teacher activity and student learning activity when applying cooperative learning model Teams Games Tournament type. In first cycle, teacher activity reached an average percentage of 64.28% and increased in second cycle to 78.57%. Student learning activities in first cycle reached an average percentage of 67.50% and increased in second cycle to 82.50%. Students’ mathematical connection ability also increases. The results of the students’ mathematical connection ability test before implementing cooperative learning model Teams Games Tournament type obtained an average score of 59.31. In first cycle, the average class value was 69.65 and increased in second cycle to 83.44. Based on the research results, it can be concluded that the application of the cooperative learning model Teams Games Tournament type can be an alternative to increase students’ mathematical connection abilities. Keywords: Cooperative Learning Model, Teams Games Tournament, Mathematical Connection Ability